Musical Drama as a Medium for Strengthening Computational Thinking of High School Students - Sukma Parousia Pieters; Rien Safrina; Deden Haerudin (International Journal of Educational Technology and Society, 2025)
This study explores the integration of musical drama as a medium to strengthen computational thinking (CT) among high school students in Jakarta. Computational thinking, a critical 21st-century skill, involves problem-solving through decomposition, pattern recognition, abstraction, and algorithmic thinking. Despite its importance, CT remains underutilized in art education. This research employs a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to design and implement a project-based learning (PjBL) framework centered on musical drama. The study involved 35 grade XI students who participated in an 8-week musical drama project, divided into creative teams to handle various production aspects. Observations, interviews, and documentation revealed that students effectively applied CT components: decomposing tasks, recognizing patterns in performance elements, simplifying complex narratives (abstraction), and organizing systematic workflows (algorithmic thinking). Results indicated significant improvements in students' logical thinking, creativity, collaboration, and confidence. The study highlights the effectiveness of musical drama as an interdisciplinary tool to enhance CT skills while fostering emotional engagement and character development. It also underscores the teacher's role as a facilitator in promoting reflective and participatory learning. The findings align with prior research on PjBL and CT, suggesting broader applicability in art education. Future research could extend this model to basic education or incorporate digital technologies.